ORGANIZATIONAL MANAGEMENT IN THE COUNTRY LOCKDOWN OF THAI BUSINESS SECTORS - Bundantanawong, Noppharat; Kalyanamitra, Kamolporn; Niyomyaht, Satit; Lakkanapichonchat, Tassanee (Journal of Educational Review Faculty of Education in MCU, 2021)
The purpose of this research were 1) to study organizational management in the country lockdown of Thai business sectors, and 2) to study problems and obstacles in organizational management in the country lockdown of Thai business sectors. It is a qualitative research using in-depth interviews with 22 key informants that selected by purposive sampling from the government executives, executives own businesses, president of the employers' Council of Thailand, president of the Federation of Thai Industries and the organization consultants. The tools used in this study was interview form, data analysis by a descriptive summary. The research results found that 1) organizational management in the country lockdown of Thai business sectors consisted of (1) management by leaders having to brainstorm solutions to problems and create opportunities for the organization, appoint a working team to have duties and responsibilities that can respond to critical operations. (2) Planning by preparing to plan for risk mitigation, adjust the work process to suit the current situation, and there are guidelines for applying technology and innovation to drive the organization and develop competitiveness. (3) Human resource management, there is safety, welfare, as well as adjustment of working styles to keep employees safe. (4) To facilitate the introduction of technology, information system and innovation to facilitate work. (5) Control and monitoring, exams and evaluating the performance at all times in order to be able to adjust and modify the operating guidelines to be able to keep up with the times. (6) Leader model, high leadership, brave to think and make a decision, have wide vision, strong and resolute. It is relied upon for employees and as the center of mind of the people in the organization. (7) decision-making patterns, must be quick and timely under all-round information, must know the purpose of the decision, and understand the situation well first. 2) Problems and obstacles is the spread of COVID-19 that is still prolonged and may take a long time, measures to help the state that are not comprehensive, and there are limited, not all business sectors are affected, and the policy to stimulate the economy is not very clear.